Determinants of Dysfunctional Audit Behavior Mediated by Job Stress - Mellani, Endy Dwi; Prastiwi, Arum (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This quantitative study aims to empirically examine the influence of time budget pressure, task complexity, and work-family conflict on dysfunctional audit behavior with job stress as a mediating variable. Using the conservation of resources theory framework, this study highlights how government internal auditors respond to various job demands that potentially threaten and/or deplete their resources. The data were collected through questionnaires distributed to 139 auditors of the Financial and Development Supervisory Agency (BPKP) and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings show that time budget pressure and task complexity trigger an increase in dysfunctional audit behavior among auditors, whereas work-family conflict does not directly lead to such behavior. Furthermore, job stress acts as a subsequent trigger and functions as a mediating variable. Task complexity and work-family conflict lead to dysfunctional audit behavior only when auditors experience job stress. In addition, time budget pressure continues to trigger dysfunctional audit behavior regardless of whether auditors experience job stress. These findings imply the need to evaluate time management policies and provide stronger psychological support for auditors to mitigate dysfunctional audit behavior